1999
DOI: 10.1007/s11746-999-0095-2
|View full text |Cite
|
Sign up to set email alerts
|

Alkylguanidine‐catalyzed heterogeneous transesterification of soybean oil

Abstract: Transesterification of soybean oil with methanol has been carried out in the presence of heterogenized alkylguanidines as catalysts. The alkylguanidines were anchored to modified polystyrene or siliceous MCM-41, encapsulated in the supercages of zeolite Y, or entrapped in SiO 2 sol-gel matrices. The catalytic activity of these catalysts was compared with that of their homogeneous counterparts, showing that the yields of methyl esters obtained in the homogeneous phase can be obtained with the guanidines anchore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 6 publications
0
29
0
1
Order By: Relevance
“…Among them special attention was paid to guanidine derivatives (see also [35][36][37][38] ), which having basicities close to carbenes do not form soaps during the reaction and their catalytic efficiencies are close to those for sodium hydroxide and methoxide (for 1,5,7-triazabicyclo[4.4.0]dec-5-ene TBD TON is no more than 270 at 70 C, 1 mol% of a catalyst, the molar ratio of rapeseed oil : methanol is 1:2.3). As can be seen from the data obtained in the present work carbenes are considerably more efficient (TON 2667 at room temperature, 0,1 mol% of a catalyst, the molar ratio of sunflower oil : methanol is 1 :20).…”
Section: Catalytic Resultsmentioning
confidence: 99%
“…Among them special attention was paid to guanidine derivatives (see also [35][36][37][38] ), which having basicities close to carbenes do not form soaps during the reaction and their catalytic efficiencies are close to those for sodium hydroxide and methoxide (for 1,5,7-triazabicyclo[4.4.0]dec-5-ene TBD TON is no more than 270 at 70 C, 1 mol% of a catalyst, the molar ratio of rapeseed oil : methanol is 1:2.3). As can be seen from the data obtained in the present work carbenes are considerably more efficient (TON 2667 at room temperature, 0,1 mol% of a catalyst, the molar ratio of sunflower oil : methanol is 1 :20).…”
Section: Catalytic Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, alkyl ester production has been limited due to the inability to compete economically because of high raw material and production costs. To improve the economic outlook of alkyl esters, the selection of raw materials, reaction conditions, and the use of efficient catalysts become critical.…”
Section: Introductionmentioning
confidence: 99%
“…Activity of non-ionic bases as catalysts for the transesterification of vegetable oils was studied by Schuchardt et al [10][11][12]. Amino acids of high basicity catalyse the homogeneous alcoholysis as the investigations of the authors have shown.…”
Section: Introductionmentioning
confidence: 99%